Development of Russian federalism in the 1990s (on the example of the Altai Territory) - M. S. Novikov (Омский научный вестник: Серия "Общество. История. Современность")
In the framework of the presented article, the author analyzes the process of acquiring the current status of the Altai Territory paying special attention to the 1990s, when this process took place in parallel with the formation of federalism in the Russian Federation. Based on the available scientific developments and introducing a wide range of sources into circulation, the author identifies features of development of federalism in the Altai Territory as part transformations of the system of socio-political and economic relations.The Altai Territory had a developed agriculture, huge prospects in the development of hydroelectric power, mining and processing industries, clearly manifested national gradation that had worsened due to the transition to market relations.During the period of federalization of the Russian Federation, society and elite put forward ideas to preserve ecological situation, to detriment of the development of hydroelectric power, mining and processing industry. Society and elite quite purposefully sought to prevent the construction of hydraulic structures on Katun River and conduct of geological exploration activities. During the period of economic reforms in the Russian Federation, local society and the elite consciously supported leftist ideas and the preservation of agriculture, which led to the victories of the red-green coalition. As a result of federalization and economic reforms in the Altai Territory, it is possible to achieve the formation of the Altai Republic and its reconstruction, avoid the industrial development of the region with all the advantages and disadvantages of this process, and prevent the collapse of large agricultural industries.